1992
DOI: 10.1063/1.463370
|View full text |Cite
|
Sign up to set email alerts
|

The short-time dynamics of molecular liquids. Instantaneous-normal-mode theory

Abstract: The molecular origins of the two-dimensional Raman spectrum of an atomic liquid. II. Instantaneousnormal-mode theoryThe anharmonic features of the short-time dynamics of fluids: The time evolution and mixing of instantaneous normal modes Since the sharply varying forces that control the arrangement of molecules in liquids are themselves intrinsically anharmonic, the natural assumption would be that any picture that regarded molecular motion as harmonic would be at best a rough phenomenological guide. This expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
91
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(92 citation statements)
references
References 41 publications
1
91
0
Order By: Relevance
“…Previous studies have indicated that taking into account only stable (real frequency) INMs does not lead to appreciable errors in the very short time dynamics of the fluid considered, and provides a better representation of the exact fluid dynamics than an all-mode treatment at longer times. [36][37][38] Here we follow the same practice and represent the water dynamics using only the subset of stable INMs. In the discussion below we refer to these modes as 'phonons', keeping in mind the limited applicability of this term in the present context.…”
Section: Transmission Through Water Described By Instantaneous Normalmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that taking into account only stable (real frequency) INMs does not lead to appreciable errors in the very short time dynamics of the fluid considered, and provides a better representation of the exact fluid dynamics than an all-mode treatment at longer times. [36][37][38] Here we follow the same practice and represent the water dynamics using only the subset of stable INMs. In the discussion below we refer to these modes as 'phonons', keeping in mind the limited applicability of this term in the present context.…”
Section: Transmission Through Water Described By Instantaneous Normalmentioning
confidence: 99%
“…Instead we use previous work that indicate that on timescales shorter than ~100fs the nuclear dynamics of different solvents, including water, can be reliably described in the instantaneous normal mode picture. [35][36][37][38] In this approach each static liquid configuration sampled from the equilibrium ensemble is used as a reference for expanding the nuclear potential up to second order in the deviations of the nuclear coordinates from this reference configuration. Diagonalizing the Hessian matrix associated with the second order derivatives of the nuclear potential about this reference point then yields a set of 'instantaneous normal modes' (INMs) whose dynamics describes the short time evolution of the liquid about that configuration.…”
Section: Transmission Through Water Described By Instantaneous Normalmentioning
confidence: 99%
“…To conclude, we briefly compare our description with the Instantaneous Normal Mode (INM) analysis of supercooled liquids [21]. A fruitful idea in the INM context is to relate diffusion to the average fraction of negative eigenvalues of the potential energy Hessian [22]: instantaneous unstable modes are interpreted as the contribution of regions with negative curvature sampled by the system in crossing potential energy barriers.…”
mentioning
confidence: 99%
“…Moreover the INM approach has been exploited to describe the dynamical features of molecular liquids (e.g. diatomic Lennard-Jones [6], CS 2 [7]) including hydrogen bonded systems like water [8,3]. On the other hand recent molecular dynamics (MD) simulations of HF have revealed peculiar dynamical features, e.g.…”
mentioning
confidence: 99%
“…As a final remark we wish to point out that the clear separation between translational and rotational components can be considered as a print of hydrogen bonded systems. In fact it is present in water and HF but not in a linear Lennard-Jones diatomic which has been investigated in [6]. To analyse in more detail the structure of the INM we need to determine which molecules participate in each given mode.…”
mentioning
confidence: 99%